Nucleotide sequences of the Pseudomonas savastanoi indoleacetic acid genes show homology with Agrobacterium tumefaciens T-DNA - Yamada, Tetsuji (1985)
We report the nucleotide sequences of iaaM and iaaH, the genetic determinants for, respectively, tryptophan 2-monooxygenase and indoleacetamide hydrolase, the enzymes that catalyze the conversion of L-tryptophan to indoleacetic acid in the tumor-forming bacterium Pseudomonas syringae pv. savastanoi. The sequence analysis indicates that the iaaM locus contains an open reading frame encoding 557 amino acids that would comprise a protein with a molecular weight of 61,783; the iaaH locus contains an open reading frame of 455 amino acids that would comprise a protein with a molecular weight of 48,515. Significant amino acid sequence homology was found between the predicted sequence of the tryptophan monooxygenase of P. savastanoi and the deduced product of the T-DNA tms-1 gene of the octopine-type plasmid pTiA6NC from Agrobacterium tumefaciens. Strong homology was found in the 25 amino acid sequence in the putative FAD-binding region of tryptophan monooxygenase. Homology was also found in the amino acid sequences representing the central regions of the putative products of iaaH and tms-2 T-DNA. The results suggest a strong similarity in the pathways for indoleacetic acid synthesis encoded by genes in P. savastanoi and in A. tumefaciens T-DNA.